2020
DOI: 10.1515/jbcpp-2019-0271
|View full text |Cite
|
Sign up to set email alerts
|

Natural limonoids protect mice from alcohol-induced liver injury

Abstract: BackgroundAlcoholic liver disease (ALD) is regarded as a global health problem with limited therapeutic options. Previous studies highlighted some anticancer, antiviral, and hepatoprotective activities of limonoids, but the effects of these compounds on ALD remain unknown. The present study aimed to evaluate the effect of some natural limonoids on ethanol-induced liver injury.MethodsThirty-five albino mice (Mus musculus) were administered with 40% ethanol in the presence or absence of the different limonoids [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, the pathogenesis of NAFLD has not yet been fully elucidated, and the determination of therapeutic targets and the advancement of drug development are severely limited. Current research shows that limonin has a wide range of pharmacological effects, including anti-cancer, anti-inflammation, anti-bacterial, anti-viral, anti-oxidation and liver protection properties ( Fan et al, 2019 ), and has been proven to have the effect of preventing and treating alcoholic fatty liver ( Valansa et al, 2020 ) and various acute liver injuries ( Mahmoud et al, 2014a ; Mahmoud et al, 2014b ; Yang et al, 2021 ). But the therapeutic potential of limonin in NAFLD is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathogenesis of NAFLD has not yet been fully elucidated, and the determination of therapeutic targets and the advancement of drug development are severely limited. Current research shows that limonin has a wide range of pharmacological effects, including anti-cancer, anti-inflammation, anti-bacterial, anti-viral, anti-oxidation and liver protection properties ( Fan et al, 2019 ), and has been proven to have the effect of preventing and treating alcoholic fatty liver ( Valansa et al, 2020 ) and various acute liver injuries ( Mahmoud et al, 2014a ; Mahmoud et al, 2014b ; Yang et al, 2021 ). But the therapeutic potential of limonin in NAFLD is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the literature indicated that limonin characterised by ZJP exhibited protective activities against long-term alcohol injury due to antioxidant and anti-inflammatory mechanisms (Valansa et al. 2020 ). Based on these results in this study and the literature on various compounds in ZJP, it can be concluded that the gastroprotective activities of ZJP were attributed to the cooperation of its multiple compounds identified by UPLC-Q-Orbitrap HRMS in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings indicate that limonoids have a protective effect on liver injury in mice. 408 In the past decade, the skin protective effect of Meliaceae plant extracts have also been further discovered. Studies have shown that nimbolide can improve the bleomycin-induced scleroderma in mice by reducing the level of collagen crosslink LOXL2, and exerting antibrosis and antiinammatory activities.…”
Section: Reviewmentioning
confidence: 99%